Islamic Finance, Consumer Protection, and Financial Stability - Lukonga, Inutu (IMF Working Papers; Working Paper ;, 2015)
Consumer protection and financial literacy are essential pillars of a well functioning and stable financial system. As the global financial crisis demonstrated, inadequate attention to consumer protection and financial literacy can lead to financial instability. Though Shari'ah principles provide a strong foundation for consumer protection, the principles alone cannot provide adequate protection because not all providers are guided by ethical precepts and the practices have deviated from the principles. To safeguard the stability of the Islamic finance industry, consumer protection frameworks that cater to the specifics of Islamic financial products should be an integral part of regulatory frameworks.